Using a satellite DNA family for species identification of commercial oysters - Lopez-flores, I.; De La Herran, R.; Garrido-ramos, M. A.; Boudry, Pierre; Ruiz-rejon, C.; Ruiz-rejon, M. (International Triennial Meeting Aquaculture 2004, 2004)
The cultivation of oyster presents some problems related with the identification and differentiation of species as Ostrea edulis (European flat oyster) with respect to Ostrea stentina (Provence oyster) or Crassostrea angulata (portuguese oyster). Crossostrea gigas (Pacific oyster). We have characterized a satellite DNA family and used it as a molecular marker for genetic differentiation between commercial and non-commercial oyster species present in Europe. This marker clearly supports a high degree of differentiation between O. edulis and O. stentina and conversely upholds the contention that C. gigas and C. angulata are the same species.